Can Private Schools Overcome Promotional Limitations through a 4P-Based Digital Marketing Strategy? A Case Study in Malaysia - Sigar, Pauline Anthony; Nguyen-Quang, Duy; Hendry, Rizal (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the strategies used in utilizing technology media used for marketing educational services and solutions to overcome obstacles in developing digital technology as a means of marketing educational services through digital technology by the sultanah engku tun aminah vocational school. Methodology: This study uses a qualitative approach with a descriptive method. Data collection was carried out through interviews, observations, and document studies. The sources of information in this interview were the Principal, Head of the Learning Resource Center, School Media Manager, Administrative Staff and Teachers. Data analysis using miles and huberman elit using triangulation techniques, namely data triangulation and method triangulation. Main Findings: The results of this study indicate that the strategy used by the st. john's private high school in utilizing digital technology as a means of marketing educational services has been running well. The strategy used by the st. john's private high school uses a comprehensive approach. The strategy used is to apply 4P (product, price, place and promotion). In addition, the consistent development process on digital media also makes the objectives of the marketing appropriate and effective and efficient. The development process is carried out to upgrade skills for PSB staff by participating in various training. Novelty/Originality of this study: The novelty of this research lies in the context of the use of digital technology in private educational institutions in Malaysia, especially in the Southeast Asian region which is still rarely used as an object of study.